Kawish urdu lasaniat for class VIIl - Iqbal, Ghulam Waris (Aligarh Publishers Lahore, 2011)
Kawish Urdu Lisaniyat explores the linguistic features, history, and development of the Urdu language, emphasizing its grammatical structure and cultural impact.